TRANSLINGUAGING IN EFL CLASSROOM AND ITS IMPACT ON STUDENT'S PERFORMANCE AT A SECONDARY SCHOOL LEVEL: A SYSTEMATIC REVIEW - La Ode Rasmin; Sahril Nur (Program Studi Pendidikan Bahasa Inggris Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Translinguaging is a phenomenon of language use where the people are bilingual or multilingual. Tanslinguaging occurs in the community and schools, both rural and urban areas. At the Indonesian secondary school level, the learning of English as a foreign language (EFL), teachers and students at schools use the target language (English) and the Indonesian language as the official language in the education system. But, local languages also occur and are used in schools for the students who have their local language, including in rural schools. This article uses the literature review method to analyze the use of translanguaging (Indonesian language, local language, and English) in EFL classrooms at schools and its effects. The author collects several national and international journals. The journal was compiled purposively, which related to translanguaging at schools. The literature review found that translinguaging in the EFL classroom influences students' performance with multilingual backgrounds (Indonesian language, local languages, and English). Therefore, translinguaging-based instruction is considered good if applied to learning English as Foreign Language (EFL).